BDNF promotes axon branching of retinal ganglion cells via miRNA-132 and p250GAP. - Marler, K; Suetterlin, P; Dopplapudi, A; Rubikaite, A; Adnan, J; Maiorano, N; Lowe, A; Thompson, I; Pathania, M; Bordey, A; Fulga, T; Van Vactor, D; et al. (2014)
A crucial step in the development of the vertebrate visual system is the branching of retinal ganglion cell (RGC) axons within their target, the superior colliculus/tectum. A major player in this process is the neurotrophin brain-derived neurotrophic factor (BDNF). However, the molecular basis for the signaling pathways mediating BDNF action is less well understood. As BDNF exerts some of its functions by controlling the expression of microRNAs (miRNAs), we investigated whether miRNAs are also involved in BDNF-mediated retinal axon branching. Here, we demonstrate that the expression pattern of miRNA-132 in the retina is consistent with its involvement in this process, and that BDNF induces the upregulation of miRNA-132 in retinal cultures. Furthermore, in vitro gain-of-function and loss-of-function approaches in retinal cultures reveal that miRNA-132 mediates axon branching downstream of BDNF. A known target of miRNA-132 is the Rho family GTPase-activating protein, p250GAP. We find that p250GAP is expressed in RGC axons and mediates the effects of miRNA-132 in BDNF-induced branching. BDNF treatment or overexpression of miRNA-132 leads to a reduction in p250GAP protein levels in retinal cultures, whereas the overexpression of p250GAP abolishes BDNF-induced branching. Finally, we used a loss-of-function approach to show that miRNA-132 affects the maturation of RGC termination zones in the mouse superior colliculus in vivo, while their topographic targeting remains intact. Together, our data indicate that BDNF promotes RGC axon branching during retinocollicular/tectal map formation via upregulation of miRNA-132, which in turn downregulates p250GAP.